Oral history interview with Dimitris Eleftheroglou / Interviewee Eleftheroglou, Dimitris Date interview: 2014 November 11 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation (United States Holocaust Memorial Museum, 2014)
Interviewee Eleftheroglou, Dimitris Date interview: 2014 November 11 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation: You but the church, the church is the only place in the world where I attend and I was invited I was invited to take part in family missidays. 3,2,1 Nathan Reddy Good morning Good morning Thank you very much for meeting us What is your name? My name is Dimitris Eleftheroglou When were you born Mr. Eleftheroglou? In the month of February 1931 And in which city? Dimitris Eleftheroglou After you were born, in which part of the city did you live? In the central part of the city, on the main road Our house was on Venizelos street, 41, 43, something like that When did you realize that you have Jewish neighbors among other neighbors? Since I was a child, because in our neighborhood there were many shops and Jewish houses In the front, on the main road where we lived, and in the back there were many neighbors What was your relationship with the Jews? I can say that we loved each other, because since we were children we played with them As children we had fights, we had friends, we had all these things What happens in general in the childhood of all children And your family was Jewish? Yes, my father especially, because he remained an orphan since he was a child He worked in a Jewish shop He learned Jewish from scratch, the Jews were the so-called Spanish at that time And from then on, we had contact, exchanges, and various things Did you learn the Spanish-Jewish? To be honest, I learned a few words, from Venna Kiefer, come here, something like that And something else, and experiments Did the children who were at your age speak this language? They spoke Greek fluently, because in school I had a classmate And in the neighborhood all the children spoke Greek Apart from that, what was your relationship? Apart from school and the children you play with, what was the relationship between your family and the Jews? Look, the families at that time were closed in some way Because a large part of the family were farmers, 95% I can say And these people did not have the opportunity to have social contact with each other Because from morning to night in the fields, the women did not have anything to pay, to take care of the children And the men, of course, turning from the fields, they threw a little water on the face and on the legs They went to the cafe, to listen to the guide, or anything else, and to drink water there, they say As I told you, I will look at the pre-interview, to note you on what you had told us before Did you have any professional relationships? Mr. Lefteroglou, we have a technical problem and we would ask you if you could talk to us without your glasses Of course And we continue, I would like to know, because I remember from the pre-interview that you had told us That your father had some professional relationship with the Jews Can you tell us exactly what it was? Yes, I can tell you, thank you So, until he became a soldier, he worked in Jewish shops, and at the same time he had small farm work But after his return from the army, he turned to his Jewish friends and told them that he wanted to open a shop And they told him, thank you, we will help you to buy whatever you want, and whenever you want, we will pay And so my father started the shop, and it went well until he was 40 years old Now we start the case from 23, 24, and then until he was 40 years old So you have a pre-history in your family of good relationships with the Jews, from your father's stories and your father's relationships Of course, of course Did they all have the same relations with the Jews in the town hall, or were there people who did not? I can say that those who were in the market, those who were engaged in business Either food, bakeries, raftades, hangars and so on, very few of them had contacts and exchanges Usually the main business was held by the Jews, the heavy trade They imported from Constantinople, they brought the fish, the turiki, the mackerel, etc, So it was distributed to the smaller shops, as well as to the furniture shops. The Jews owned all of them, very rich shops with a lot of commerce in them. Apart from the commerce, was there anything else, was there another area in the Municipality where the Jews were mainly involved? Apart from the commerce, there were various meetings, when there was a dance or any social event, they participated, because the young men of that time and the older ones, of course, they made friends in songs, in celebrations and so on. I mean, in the economic sector, that is, industry, commerce, professions and so on. So, the big industry was the middle class. Some name, Givre, had factories in Suflis, but the area of the Municipality, all of Eurus in general, had workshops, workshops, which were made by the middle class, and the middle class, as they are known, they produced the middle class. The people were involved, and then they gathered, they gathered various small shops and they gave them to the Givre factory, and from there the middle class came out. What were the relations, what did you hear from these people who cooperated with the Givredes, with the other Eurus merchants, did they have all the labor relations with them? Look, of course, among the communities there was a collaboration. One of the Givredes was called like this, the Armenian like this, the Ottoman like this, because it was a city that had many ethnicities. So, these interactions, as they happen today, among them, there is a little racism, but let's say it on the positive side, not on the negative side. Do you understand? Mr. Dimitris, I would like you to tell me a little about the school, how you were with the children, how the teachers were, how many children there were in your class, did you play any special games with them? We didn't play very much, but all together, we and the Eurus, we made teams, and we played, either they called it the Klososkoufi, a place to play in the neighborhood, or various other games of that era. Did you make teams, the Christians with the Jews? No, no, there was no such thing. We were all mixed up. Was there anyone in your class who made negative comments about the Jews? Look, as I said before, there were, I was characterized by the other gypsies, or the other, I don't know, dirty people, and so on. Such things, these little things. I ask you, because in certain cities, have you been told that the week, the big week, I don't know if it happened in the municipality. Indeed, the big week, unfortunately, there was a religious fanaticism. At least from us. Our grandmothers and our grandfathers always kept this thing. It was a passionate religious feeling. Can you describe it to us? What were they saying? Don't go through the Jewish neighborhood, because if they catch you, they will put you in the and from there, such things. But such a thing never happened. And we heard these things from each other. But, of course, there was a fanaticism. In your family, was there a grandmother who said that? My grandmother never said such things to me, but I heard other women say these things. And the children, how did they ignore it? I can say that they ignored it. I'm sorry to interrupt you, but the big week, did you also play with the Jews? We played, but the little children were frightened. How can I put it? They were afraid, the little ones, but the bigger ones, they didn't care. I would like to go a little bit to the occupation period. How did life change in the Second Republic during the occupation period? What exactly happened? You must have been about 10 years old when you were born in 1931. So, in 1941, in the spring, the Germans came to the Second Republic. Of course, from what there was information, and the little radios that were circulating then, either sugar mills or restaurants, we were listening to the news. After the collapse of the Albanian front, we saw that things started to deteriorate. And unfortunately, everyone was waiting for the Germans. Mr. Dimitris, did you see, with your own eyes, the Germans entering the Second Republic? Exactly. Because our house was in the center, and when the Germans entered, I remember, there was a roundabout in front of our house, we were looking through the grilles, while the Germans were entering, no one was walking on the streets, but then, inevitably, people had to start their lives again, their work, one thing after another, and they began to circulate, but all together, I can say, with a wave, to prevail everywhere. What exactly changed in your family life, after the Germans entered and afterwards? Everything changed. From a moral point of view, of course, there was no... There was a lot of chaos. From a moral point of view, there was a lot of chaos. Those who had savings with money, the thousands, I remember, of Georgi Stavros, who had a lot of value, because one thousand of Georgi Stavros was paid by a public employee. When the bread had half a drachma, we would see half a drachma on the first day, one drachma on the second, three drachmas on the third, and so on. So, those who had savings with money, those who had a lot of money, were the most expensive. Among them was my father, who had a box with a thousand of Georgi Stavros. And what happened? In your professional life, what happened to your father? How did he react? My father had two shops, one in Bakaliko, and one in Manadeko, next to it. And in the middle was the entrance to the house. First of all, there were no shops to buy and to sell to the customers. There was nothing. Why was that necessary? It was necessary because the Germans, whatever they could get, they took it. It was either animals from the stables of the people, or it was wheat flour and so on. They collected all of that, and the people were trying to survive. All the shops were closed, they couldn't sell anything. People didn't have money anymore, because it wasn't worth it. We reached the point, that is, a thousand after five months, six months, not to buy even a pack of cigarettes, they didn't even have cigarettes back then. There was only smoke. They put the smoke in a paper, and sold it like a watch, let's say. I remember from your interview, you told us that the owners of the father had approached him, and they tried to exchange with him. Yes. Because we had Bakaliko and Manadeko, he gave a very good position, both in terms of commerce and education. As soon as the Germans entered, they saw that they could... They bought the first day, and the exchange lasted for a week, but my father didn't like this exchange. So he turned to a neighbor, who was asking for opportunities. He said to him, don't you take over this job? And he said, thank you. Since then, my father didn't even keep his exchange with the Germans for a week, and from then on, he took over. And he got to the point, where he became the owner of that company, which was very bad for all of us. The villagers? Yes, the locals. The citizens. Yes, the citizens. Did you have any other relationship with your father? I remember that your father had a prejudice against him. They were friends since they were young. But my father couldn't understand that this man would get to this point. And he told him, take it easy, I don't want to have an exchange with the Germans. And of course, he gladly accepted all of this. Didn't your father warn him that after the liberation... Of course, on the brink of the German expansion, he and his family and his father thought that the Third Reich would live for a thousand years. And his father said, take it easy in the cities. In the cities, they told him. Take it easy. In one day, they would leave. It's impossible for them to leave. They would live for a thousand years, and so on. I tell you, the good thing is that my father respected him, he feared him, he respected him, and many times he was angry. And my father told him, take it easy. But he didn't listen to anything. And in what other way did this Ostamboli cooperate with the former occupation? Simply, when my father told them about Ostamboli, he approached them and told them to take it. He can't serve you. Yes, you said before that he did other bad things, besides cooperation. Then it happened. Then it all happened. That is, you can tell me, did you see something with your own eyes that he humiliated people, humiliated Jews? From what I heard from my father, stories? You didn't see. When I was young, I couldn't listen to all that. Yes, what did your father say? He would go with German camions to various villages, he would see a calf in a stable, he would take them, he would give them a piece of land, he would pay them, he would take them, he would collect all the agricultural goods. And he was, he had entered the eyes of the whole world. As for the Jews, did he humiliate Jews? I can't say that, because I don't remember now. Anna, here we are a little confused, chronologically. I can't say if he was responsible, if he did this job for the Jews, but he humiliated our own people. So it makes sense. It makes sense. What was his name exactly? Stambolis? Stambolis, I think he was called Sulidis. Sulidis. I think he was called Sulidis. This, as a result, after the Germans had overthrown him, he went to Thessaloniki. In Thessaloniki he was tried, of course, after the trial and he was convicted. Seven or eight years later, there were agricultural prisons, and then they set him free. How long did they set him free? Seven years, six years, after seven years of imprisonment. How did you learn that? Did you go back to the village? No, I didn't dare to go back to the village, because the rest of the people, I'm sorry about that. Yes, you're right. Yes, because the rest of the people had him in their eyes, because they could have killed him. I didn't dare. He stayed in Thessaloniki for many years, and then, in his old eyes, he probably went for a walk. So, in some way, everyone had been wronged by him? Not only those who were not wronged, but every action he took was unacceptable. Now I want to go to the Jews. What do you remember? How did your life change for your classmates, for your friends, after the Germans entered the town hall? What did you see that changed? After some time had passed, we saw that in all the Jewish houses they marked with the letter A, with a black color. This thing, of course, had been reported. The Jewish community had been informed that something was happening. But I can't explain it, because my father told his neighbors and his Jewish friends, let's cross the river Ebro across from Turkey, and from there, through Turkey, to find Palestine. I can't understand why they didn't accept it. And he specifically told them, I have a branch in the town hall, as I said before, the shops were closed, and they had to deal with the agronomy. A little bit of calabash, a little bit of lamb, a little bit of lamb, and all that. We would load on the lamb some agronomic tools. I was wearing old clothes, I don't remember what they were called. And next to us was a family, Madame Perla, I don't remember what they were called. They were singing and crying every night, and two little children. And by the way, I don't remember what they were called. And he said to them, why are you crying? It's easy. Two or three boys and a girl left our neighborhood, and they came back from Palestine, and they left again. They had the opportunity to escape. Only this couple escaped? No, they didn't escape. Two boys and a girl who went to Palestine. How did you help them? There was an organization that came into contact with Adrianople. There were two groups, the English group and the German group. When the Germans advanced, this was the policy that the Turks played and continued to play today. That is, when they advanced, certain groups were leaving. Many Greeks were leaving from then on. The entire Greek Constitution passed after the collapse of the Albanian Bridge. We handed them over to the Germans. But when the signs began to light up the lands and to advance, then they played it as we say, as we say in English. Did you see who helped this Jewish couple to pass across? From what I know, of course, I personally cannot say it, because I could not know everything and these things were secret. It seems that there were connections that we communicated because the English certainly wanted people to create it. Who did you know? From the parents? From the father? Of course, you did not see it. I did not see it, but after the Germans and so on, then it began to become known how one acted, how the other acted, then these things became known. But no one dared to say that I did this and I did that. Do you remember her accusation? I can not remember. You say that this family was crying and so on. What were they commenting in your house? We were sorry for them, we sympathized with them. Your father said something to them? Yes, he did. Did you hear it with your own ears? What did he say? When we were talking at home, my mother said, I can go to them across the river, not to go with them, but to go to them across the river. Was your father organized? After a year, my father was organized when the resistance began. He was organized and I think he had the connection between Greece and the city. And especially me as a child, I can not understand what confidence they had in me. But we were raving at that time very early. Think now, 12-year-old child, 11-year-old child, to put in my body various complaints and to go to some stores that knew that the resistance was organized. Were there other children in your family? There were, but we do not know what each other does. It all happened in a cinematic way. And I will tell you one case, I remember it and I laugh, of course, they try to self-sarcastic. My father says to me, we had a little boat about three kilometers from the city. He says to me, there is a connection which is associated with Greece. Greece was the army, the revolutionary army of the revolution or resistance in general. Everyone participated in Greece. There was no distinction, left, right, etc. Everyone had a desire to throw the Germans out. He says to me, you will go to Gaidora, you will go to Belli, take these applications and you will go there, you will wait for you under the bridge. I go out of the city, I meet a truck with Germans next to it, soldiers. What can I do? I put my hand on it and I raise my hand and I shout, Hi Hitler! I want to surprise them. But I lost track of time. As soon as I go to Belli, Constantine Sopourialis sees me as an agent. He says to me, what happened to you, Dimitri? I say, what was going to happen? He says, I remember and I laugh at this period. Did you have other such episodes that you were afraid of? When do these happen? We had other episodes because they collected if there was any block outside in the mountains. In Evros we did not have big mountains. They made an episode with 10-15 people in the square and they shot them. What year do these happen? Now, 1943. Do you remember the gathering of Jews? I remember a case when I was in school, at the gymnasium. A bus came, I do not remember who it was, and informed the school that the children would not go to their home but to the synagogue. Where was the synagogue? Did you go? The synagogue was close. The Jewish neighborhoods, the center, everything was close. I cannot say it was far. The synagogue was 500 meters from the school. From there with the cars and the train they went to the synagogue. Did you see these? As far as I know, when I saw them, we tried to approach them and give them water, because they were all our friends, most of the children and the well-known families. We did not know if there was a religious difference between them. Were there women in the synagogue? All women, everything. Do you remember how many days they were there? I cannot remember. Was it more than one day? It must have been one or two days. Did you manage to give water to someone? I approached because the Germans had no way to give me the well with water. From there I followed them until they reached the camp. But others, according to information, put them in wagons where they put the animals together. Did you follow them? Until they reached the camp. Do you remember how they were taken out and how they were carried to the camp? It was a well that started from the synagogue because the synagogue was about one and a half kilometers long. Until the middle of the road I went from there and we started to go back. We were small children. Of course, they did not dare to go outside. You tell me that only the children followed the well. How many people were in this well? I can not remember the total number of people. Because it was a large area. Did you know them? Many of them, almost all of them. Almost all of them. How did they behave in the well? What did they behave? People were confused. They did not understand why they could not leave the camp. They had the opportunity to leave the camp. I do not know if it is true but it is said that some Arabs told them not to leave because they were not going to harm us. They just wanted to go to Poland to become a state. They lied to them. This is what they should do. There were people who escaped from the well. No one could escape. Were they all Jews of the Second Municipality? Yes, all of them. Did anyone from those who left the well go to the train or to the station? Where did they go? From the train they started from the Second Municipality all the way to Thessaloniki. Mr. Dimitris, what month was that? Do you remember? I cannot remember. Was it 1942? No, you told me before that it was 1943. It was 1943. The resistance began. But the Jewish element had already left. And they went to Thessaloniki. Did anyone from those who left the well go to the station? Yes, I can remember some people. It was a family, three girls and the father. Do you remember any names? Yes, I remember the names of the two girls. One was called Kolomba. The other was called Suzy. Their father was called Israel. His father fell when he was in the first civil war and he had a lot of friends with my father. He escaped from all the troops. From what I learned from the story of Ildes and his children, one of them was a beautiful girl I don't remember her name, Kolomba. The German soldier had her at home and she managed to get the other two sisters. Of course, their mother and father were found in another camp. But the father, Israel, saved them. And when I came to Deirut, for a month, every day, at my father's shop, the events of that time were taking place. All those bad years that we went through. You were listening to this with your own eyes. You were at your father's shop. Yes, at his father's shop. And neighbors came to see what this man was doing. I have an impression, and I want to ask you again, that your father was organized in the resistance of Poles. He had many Jewish friends who had trusted him and with their help he opened two shops. This happened much earlier. Yes. This means that there was mutual trust between the Jews and the father. When, before they left, he could not help any of them, they did not trust him to help them to escape? They did not expect that they would have this ending. This is the bad thing. Because they had the opportunity and they had money. They had the opportunity because the Turks were the so-called garrison guards. If you threw them a gold coin, they would take you. They had the opportunity and with money they could pass. Do you remember your father encouraging them? Exactly. I will tell you until the 8th of April when the Eurus was spreading it was an easy passage. Of course, it was a dangerous passage because there were gunfire and so on. What happened when the Jews left for the West Bank? All the Jewish houses were sealed and they made an order and they said that whoever dared to rob one of these houses would be killed. Of course, someone entered one of these houses and the next day he was killed because they were looking for the treasure. Who entered these houses? No one. The Germans did not enter? The Germans took the houses that they were interested in. Those that were in good condition were used for military operations. They were two nice Jewish houses. The police called them the Gestapo. Those were the organizations. What about the shops of the Jews? The shops were closed. After the liberation the Jewish community of Thessaloniki that was in charge of all of this sold many of these to our own people and from there the shops started to work normally. What about the shops that were taken over by the people who bought them? Were they full or empty? There was nothing inside. Who took them? The Germans took them all. Only the Germans took them? Our people did not dare to take them. They were afraid of being taken over. The shops were taken over by the Germans. Did you see the end of the Germans? No, I can't tell you. They could have been taken over at night. But it happened as they say. Apart from Stambouli was there someone else? Someone else who cooperated with the Germans? Yes, there were the so-called security squads. The Germanized. Those who for some reason had no conscience joined these squads wearing German uniforms and they were much worse than the Germans themselves. Because if they had personal issues with each other or someone was jealous of them they would get rid of each other. Many people were killed. When did the security squads become a part of the district? After the demolition of the district. After a short period of time. But they kept Chorofilaki. And I remember... From what I understand the security squads and Chorofilaki were different. Chorofilaki cooperated with the Germans? Chorofilaki tried to play a patriotic role. But it was forced. They had to act according to rules. To whom were Chorofilaki forced? To the security squads? No, the Germans wanted... They had the demand from the Greek Chorofilaki to take more drastic measures against the Greeks who were breaking the law. I remember one case. It was a certain Nomarchis who was a patriot. When we say a patriot he was helping the people. We learn that the whole Chorofilaki district was recognized by the Greek side at the end of the 19th century. I remember I was with my father in Bakhce. Bakhce is the district with the districts. What's going on? What is this? I don't know. Are they investigating? We learn the next day that the whole Chorofilaki district was recognized. You almost saw it with your own eyes. Do you remember after the liberation when the people who were hidden had left how many Jews came back? About 8-10 people. I can say some names. We would like that. One of them was Josef Taramboulous who escaped and took one of the two girls from the three girls I don't remember Sultana, what was her name? They were Kolomba and Suzy. I think Sultana, I'm not sure. She got married. Someone else Solomon Behar who was a merchant and we had exchanges. They stayed but they left when they were old because their children got married in the month of Thessaloniki so they had the property and they found it again. It was also a shocking event. Some family fathers were doctors they called them and their son was saved. But what did the Germans do? They humiliated him in front of his father's eyes. Did you hear that? Yes, because when he came he saved him. He didn't hide it he didn't hide it. We all saw him with great sympathy. That old man. Was there a Jewish in the municipality or a mixed marriage that was saved during the occupation? I remember one case but I can't remember someone called Isidore from my mother and from us I remember people were trying to convince him he has written his last name he is a Christian and he was a mixed marriage the mother didn't escape the father I don't remember if he had a dead wife but I don't remember what happened to the young man I can't remember In your previous interview you told us that the whole village was saved and they didn't take Isidore and that he was saved I don't remember if he was saved because he was lost Do you remember names? There were others besides Behar There was a Jew who was one of the three who went to Palestine From the couple The girl and the... It wasn't a couple It was irrelevant He was saved and then he came He opened a big shop and until the last time I was there he continued to work very well And his son Dr. Nahon left the city They all went to Thessaloniki because selling all the shops the houses the community of Thessaloniki had the opportunity and all the children were married Is there anything else that you would like to tell us about this period in relation to your country and the situation during the occupation? If there is something that interests us more I can tell you this Because there was a radio in the square of the Municipality that broadcasted every afternoon at 7 pm the Berlin broadcast of the Athens Radio Station And because the elders didn't dare to go to listen because as soon as there was an episode with the standards they could be caught And they sent me and our neighbor a wonderful man they lined up our yards and we had a small room that in a way was not isolated and beyond that because the guy who was broadcasting the newspapers was controlled by the Germans and every time every day they presented maps of Europe to the Germans they had reached Stalingrad then the Germans I went there every night listening to the radio I had the opportunity to translate what I heard I didn't have the opportunity to criticize and my father of course was a third party but he had the experience of life and so on he had the map in front of me and he told me this was happening for 20 days I remember specifically and they were using they were cleaning the German the military forces are there they will take over Stalingrad this was happening for 20 days my father was saying to Barban Nikolaj next to him they will find a dark German in a little while we will understand and from there we understood that something is happening something pleasant is happening and indeed things started to change of course there were no radio stations the 5, 6, 10 that were in the city the Germans took them no one managed to hide it what I learned from the resistance if they had a radio station that's it is there as far as you know a Jew who was hiding in the occupation in the municipality those who left who passed through Turkey after the liberation did you meet with anyone your classmate, your friend I personally did not meet because none of my classmates came back these were the older guys 5, 10 years older but they continued to be with our friends of history of fun there was no conflict between them we thank you very much Mr. Eleftheroglou your testimony is very valuable and we hope to meet again and to give you the video recording please, please it was a pleasure because I really liked these people and I still like them because the Jewish people and the Greek people are the oldest people in the Mediterranean something connects us but there was always a contradiction I am smart and the others are smart today from what I see something is going to happen something is going to happen and this is very nice these meetings that take place on a high level we thank you very much Mr. Eleftheroglou and we hope to meet again please Mr. Eleftheroglou from the last time we talked about the break there were some points that were not clear and I would like if you can explain for example you as you watch the broadcast you saw with your eyes your neighbors how they are leaving and the reason I ask you is because you told me that they would give you a souvenir if there was something else can you tell us this scene again? yes and something I forgot to say and another neighbor gave my sister a bracelet this detail and the name I told you Madame Perla the men called him Iakovos Iakovos was Changaris or someone else Iakovos was Changaris and he lived next to us can you tell us how the farewell was? what were these people carrying? how were they connected with the bomb? did they go to the synagogue from their home? I didn't see this movement I don't know what time it was but they couldn't take anything more than a stick and nothing more the children in the school your classmates what time were they notified to go to the synagogue? before noon before noon they would go to school at noon at 10 or 11 so they kept their books in their bags and went to the synagogue then the people in the bomb what did they keep? whatever they could take and whatever they were told to take from a bag anything they could take you saw them yes you said you recognized some faces do you remember some names? the names were the couple I told you before and other names and other people I remember them who accompanied these people? it was a German detachment among them there were many Austrians the Austrians in a way they were more tolerant more exchangeable they were trying if they could to help to turn a blind eye why turn a blind eye? in extreme cases if they could do something that was good for them to help and now I remembered another that I didn't say the other time we had a man older than me about 10 years his name was Hatzinikolaou Nikolaou he became a good protagonist in the Greek scene who played the guitar from the 6th grade and he told me he told me the same when he was passing by a house that the Germans had and it was Austrian and because they called him he played the guitar how did they call him the great Italian tenor the years after I will always remember so he went inside to listen to London the London radio station and indeed this man is still alive and we are still talking but he has lost it he has lost his mind and he was listening to the news of London the station that only he could and they went out they were watching and he managed to transfer the news that he was listening from the radio station I mean the Austrians made a blind eye and one of them gave him his ID and went to Vienna after years did you have a similar personal or negative experience from the Germans yes, I had personal experience from an Austrian doctor that was in our neighborhood so a farm tool that we call a dicranium because in the occupation we had two tools we went to the fields and I climbed on a farm and with my patience I entered and this doctor saved me the only Austrian doctor and this doctor was Austrian while when the liberals came and gathered all the Germans they left him with the cars and when the Germans crossed the bridge he was riding a horse they appreciated the help that he brought he was a real doctor he didn't care and on the contrary did you have a negative experience from a German personal experience yes, I forgot to tell you in front of our house it was a night a group of our friends wanted to have acquaintances with Germans and now I can't describe it from a humble point of view and I was a kid I didn't go to listen to the Germans and the Germans knew three languages Turkish, Bulgarian I think he was Bulgarian and the Greek and he said that he was going to Turkey and he was going to the inn and he was giving information and he started beating me and beating me and how did you feel? how did I feel? what can I say I go to my father and he says it was necessary because they were Greeks and they were talking with them I would like to ask you about the gendarmerie if you saw them what was their role in the society of the municipality in relation to the conquerors because you told me before that they were worse yes, worse you had a personal experience you watched something what did they do? because what was happening was happening at night or in the late hours they would go to houses when they saw someone who didn't like their face or they wanted to rape they would take something if they didn't like their face they would take it they cooperated with the antarctic I understand do you remember who accompanied the Jews in the trains? who accompanied them? the German there was also Austria only Austria I think there was also Hungary but in Hungary they were used in the transports they had horses were there Greeks who accompanied the Jews? were there Greeks from the gendarmerie? no, because the gendarmerie was created later when? after the Jews were exterminated yes, after I would also like to ask if there was someone who escaped other than the Jews from the gendarmerie because you told me there were Christians who escaped did you know people? did you see people? I can tell you there was a man Grigory Grigoryos who is now a Maccariot Angelides Stavros I remember those guys they went and joined the allied forces in Palestine did you know someone else? yes, I forgot the most important Maccariot teacher the first years when I went to high school 1941 he was the principal and he I remember now in 6 months in 1 year he managed to pass through Eurus and found himself in Palestine I think all the questions I had were clarified and I thank you very much for this discussion with the first opportunity we will communicate again please, I wanted to complete I forgot to mention my compatriot the tenor who played a very important role please, tell us not what I told you before the house where the Germans lived and because he played them classical music classical music they had him and they had him I told you before and he was watching and he brought the new songs thank you very nice thank you again this was very important Mr. Dimitris I would like to ask you if you know how this organization was created were they volunteers or were they appointed by the Germans? they were volunteers volunteers people of opportunity without loans without patriotism they were trying to get rid of the occupation thinking that the Third Reich will last for a thousand years and I would like to ask you if you had any personal experience with them or if you listen to a story of another person who was attacked or died because of them what I have heard from my father we had a customer from a village who was working the security forces gave him whatever he had and the German soldier went to the village with a metal helmet and they caught him the security forces proved it and these were the security forces as long as the Hellas lasted about 6 months and then came the civil war between us and this unfortunately came back to the state and got the best awards all collaborators with the Germans and all those who fought against the Germans were executed it is a sad thing a very sad thing I hear it and I feel it I hear it and I feel it and I feel the same Mr. Dimitris the resistance the Hellas judged in many places those who cooperated with the conqueror in the case of the security forces and the traitor that you said, Stamboli who followed the Germans betrayed and took advantage what happened after the liberation with the security forces the security forces let me ask you who liberated the municipality the Hellas the Hellas when they entered the municipality were the security forces there? some of them disappeared I remember the leader of the security forces he was held in a basement and to get him out the Hellas were trying to get him out when they got him out they killed him they dragged him to the municipality the revenge was good it was a great scene were there other cases like this of the security forces that were punished by the Hellas? I remember some cases they didn't kill them but they had their prisoners and they used them for help to transport the cargoes and other things and some of the guards who were warmly cooperated with the Germans those who wanted to leave, left did you know such guards? how did you see them cooperating with the Germans? how can I tell you it was like a flashlight one of them was listening were there Greek guards helping the Germans no I only remember the Germans thank you again thank you